2008
DOI: 10.1007/s12010-008-8387-9
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Immobilization of α-Galactosidase from Penicillium griseoroseum and its Application in Oligosaccharides Hydrolysis

Abstract: Partially purified alpha-Galactosidase from Penicillium griseoroseum was immobilized onto modified silica using glutaraldehyde linkages. The effective activity of immobilized enzyme was 33%. Free and immobilized alpha-galactosidase showed optimal activity at 45 degrees C and pH values of 5 and 4, respectively. Immobilized alpha-galactosidase was more stable at higher temperatures and pH values. Immobilized alpha-galactosidase from P. griseoroseum maintained 100% activity after 24 h of incubation at 40 degrees … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…However, the Sephadex-bound galactosidase conjugate showed considerable enhancement in the thermal stability [20]. Immobilized a-galactosidase of P. griseoroseum maintained 100% activity after 24 h of incubation at 40°C, while free enzyme showed only 32% activity under the same incubation conditions [8]. Therefore, the higher stability of crosslinked Con A-a-galactosidase entrapped complex would be exploited in hydrolysis of soymilk where the chances of contamination is very much reduced.…”
Section: Resultsmentioning
confidence: 99%
“…However, the Sephadex-bound galactosidase conjugate showed considerable enhancement in the thermal stability [20]. Immobilized a-galactosidase of P. griseoroseum maintained 100% activity after 24 h of incubation at 40°C, while free enzyme showed only 32% activity under the same incubation conditions [8]. Therefore, the higher stability of crosslinked Con A-a-galactosidase entrapped complex would be exploited in hydrolysis of soymilk where the chances of contamination is very much reduced.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the α-galacto-oligosaccharides pass into the large intestine, where the resident microbita ferment them into carbon dioxide, hydrogen, and methane, which lead to flatulence and gastrointestinal disorder (Steggerda et al, 1966; Prashanth and Mulimani, 2005). Accordingly, degradation of the oligosaccharides from the soybean-based products by α-galactosidase could be an efficacious tool to solve the nutritional problem (Ghazi et al, 2003; Gote et al, 2004; Falkoski et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Considerable attention has been paid to immobilized enzymes, because of their favorable features such as reusability, stability, and separation of the enzymes from products, compared to free counterparts (Falkoski et al, 2009). Particularly, concerning animal nutrition and feed science, the immobilization technique has been applied in developing a kit for measuring in vitro amino acid digestibility of soybean meal, which could be correlated to poultry true amino acid digestibility (Schasteen et al, 2007) and in preparing a forage additive (Monica et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The immobilized enzyme showed an optimum reaction at temperatures between 35 and 40°C, whereas free enzyme had an optimum temperature of about 35°C. This shift toward higher temperatures with adsorbed uricase could be explained by multipoint non-covalent interactions, which consequently leads to an increase in the activation energy of the enzyme to reorganize an optimum conformation for binding to its substrate [32][33][34][35][36]. Therefore, it is concluded that the adsorption caused a significant improvement in the thermal stability of uricase.…”
Section: Immobilization Of Uricase On the Conductive Filmsmentioning
confidence: 98%